Economic and ethnic polarisation among children in Sweden's three metropolitan areas - Danuta Biterman; Björn Gustafsson; Torun Österberg (Institute for the Study of Labor (IZA), 2007)
This paper investigates certain issues of economic and ethnic segregation from the perspective of children in the three metropolitan regions of Sweden by using a relative new operationalization of the neighbourhood concept. Neighbourhoods are clustered by population share of visible immigrants in proportion to share of native born residents. The target variable under study is child income based on income of parents. Inequality in child income 1990, 1996 and 2002 is studied by decomposing additively decomposable inequality indexes. Based on this, measures of residential economic polarisation and residential ethnic polarisation are obtained. Of major significance is that residential polarisation increased for all three regions and for both sub-periods 1990-1996 and 1996-2002. For example, while in the Stockholm region 7 percent of inequality in child income in 1990 was due to differences in mean income across neighbourhoods, the proportion had increased to as much as 22 percent in 2002. Ethnic residential polarisation increased as well and we report a relatively large overlap between economic and ethnic polarisation. Based on estimated regression models, we conclude that increased returns to parental education have forcefully contributed to larger economic polarisation among children in Swedish metropolitan regions.
Keywords: D31; 330; Segregation; children; Sweden; immigrants; income; education; Segregation; Kinder; Migranten; Ethnische Beziehungen; Nachbarschaftsökonomie; Ballungsraum; Schweden